A new mouthless marine nematode from Fiji - Kito, K. (Journal of Natural History, 1989)
Parastomonema fijiense gen. nov. et sp. nov. is described based on specimens obtained from coarse tidal sand on a coral reef in Viti Levu, Fiji. Parastomonema is the second mouthless genus of the family Siphonolaimidae and it is differentiated from the other genus Astomonema by the 0+0+4 configuration ofhead sensilla and the paired testes